2012
DOI: 10.1021/jp306498b
|View full text |Cite
|
Sign up to set email alerts
|

Large Ultrathin Anatase TiO2 Nanosheets with Exposed {001} Facets on Graphene for Enhanced Visible Light Photocatalytic Activity

Abstract: Tailored synthesis of well-defined anatase TiO2 nanocrystals with a high percentage of reactive facets has attracted widespread attention due to the scientific and technological importance. Here, high-quality nanosized anatase ultrathin TiO2 nanosheets, mainly dominated by {001} facets, were grown on graphene nanosheets by a simple one-pot solvothermal synthetic route. The obtained samples were characterized by X-ray diffraction (XRD), transmission electron microscopy (TEM), high-resolution transmission electr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
136
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 342 publications
(145 citation statements)
references
References 67 publications
8
136
1
Order By: Relevance
“…Thus, a proper combination of graphene and TiO2 would give rise to nanocomposites exhibiting the properties of the respective building nanoscaled components with eventual synergetic effect allowing high efficiency for specific applications. A fairly large number of preparation methods of nanocomposites obtained from TiO2 and graphene for photocatalytic applications have been reported which include thermal and solvothermal reactions, sol-gel route [24,25], hydrolysis, impregnation, liquid phase deposition [26][27][28].…”
Section: Introductionmentioning
confidence: 99%
“…Thus, a proper combination of graphene and TiO2 would give rise to nanocomposites exhibiting the properties of the respective building nanoscaled components with eventual synergetic effect allowing high efficiency for specific applications. A fairly large number of preparation methods of nanocomposites obtained from TiO2 and graphene for photocatalytic applications have been reported which include thermal and solvothermal reactions, sol-gel route [24,25], hydrolysis, impregnation, liquid phase deposition [26][27][28].…”
Section: Introductionmentioning
confidence: 99%
“…Nanosheets of various layered metal oxides have been prepared [6]. Layered TiO 2 has been extensively studied for its dielectric properties and photocatalytic activity [104,105]. Rutile form of TiO 2 has one of the highest dielectric constants (80-100) among the binary oxides [104].…”
Section: Metal Oxidesmentioning
confidence: 99%
“…However, studies on salinity effect on toxicity of ZnO-NPs are relatively scarce. A study on the salinity-dependent toxicity of ZnO-NPs showed that increasing in salinity from 5 to 35 PSU (practical salinity unit) decreased the dissolved Ecotoxicity of Zinc Oxide Nanoparticles in the Marine Environment 927 E zinc ion concentration due to precipitation of the metal ions and consequently reduced the toxicity to the marine copepod T. japonicus [45].…”
Section: Salinitymentioning
confidence: 99%
“…However, studies on salinity effect on toxicity of ZnO-NPs are relatively scarce. A study on the salinity-dependent toxicity of ZnO-NPs showed that increasing in salinity from 5 to 35 PSU (practical salinity unit) decreased the dissolved Ecotoxicity of Zinc Oxide Nanoparticles in the Marine Environment 927 E zinc ion concentration due to precipitation of the metal ions and consequently reduced the toxicity to the marine copepod T. japonicus [45].pH Changes in ion dissolution and aggregation size of ZnO-NPs can occur following from a change in pH. Miao et al [19] compared the toxicity of ZnO-NPs on the marine diatom T. pseudonana at different pH levels (i.e., pH 7-9) and attributed the elevated toxicity of ZnO-NPs at low pH to an increase in the release of zinc ions from ZnO-NPs in the exposure medium.…”
mentioning
confidence: 99%